Florida Nursery and Landscape Industry Economic Contributions Report - Hayk Khachatryan; Melinda Knuth; Alan Hodges; Charlie Hall (EDIS)
This report summarizes production and marketing practices and trade flows for the Florida ornamental plant grower and dealer firms for 2018. Written by Hayk Khachatryan, Melinda Knuth, Alan Hodges, and Charlie Hall, and published by the UF/IFAS Food and Resource Economics Department, February 2022.